Evaluation of the upper and lower proximal lacrimal canaliculi using spectral‐domain optical coherence tomography in normal Beagle dogs. (16th November 2021) - Shim, Jaeho; Kang, Seonmi; Lee, Eunji; Kim, Sol; Park, Jisoo; Kim, Hyelin; Seo, Kangmoon
Abstract: Objective: To confirm the feasibility of visualizing upper and lower proximal lacrimal canaliculi (LC) using spectral‐domain optical coherence tomography (SD‐OCT). Animals studied: Eight eyes of four normal Beagle dogs. Procedures: To obtain an upper proximal LC image, the head was turned in the opposite direction to the eye being imaged, and the medial part of the upper eyelid was everted to expose the LC. To obtain a lower LC image, the lower eyelid was everted just below the punctum. Using "angle mode", the scan line was placed parallel on the long axis of the LC. The inlet LC width (LCW) was measured. Artificial tears (AT) were instilled, and LCW was compared before and after AT instillation. Additionally, the return time to the initial LCW inlet width was recorded. Results: Before AT instillation, there was a significant difference between the mean upper and lower LCW (91.8 ± 3.2 µm and 110.1 ± 8.4 µm, respectively). After AT instillation, the mean upper and lower LCW were 236.9 ± 27.7 µm and 238.4 ± 30.4 µm, respectively. Significant differences in the LCW before and after AT instillation in both the upper and lower LCWs were observed. The mean return time of the upper and lower LCW to their initial widths after AT instillation was within 4 min. Conclusions: Spectral‐domain optical coherence tomography was an effective method for providing high‐resolution images of the upper and lower proximal LC. This method enables observation of LC changes after instillation of eyedrops in veterinary clinical practice.